Analysis of Medan Sunggal Sub District Urban Spatial - Dewi Arini (Talenta Publisher, 2020)
This study is intended to determine the state of the spatial urban city in an area. This analysis aims to determine the morphological face of the city to determine the movement and development of the city in the future. The study area is located in Medan Sunggal Sub District. Medan Sunggal sub-district is one of the sub-districts in the city of Medan which borders Deli Serdang. According to the RTRW for Medan City, this area has a land-use as a residential area, but there is also economic growth in the form of commercial areas along the roads in all villages in Medan Sunggal sub-district. The discussion on urban spatial analysis in Medan Sunggal sub-district uses figure-ground analysis and Von Thunen's zone theory.